(untitled) (Hoboken, N.J., 2007)
A detailed, up-to-date review of transition metal-containing polymers. Promising advances in the electrical, optical, magnetic, biological, and catalytic properties that metal-containing polymers possess have led to notable expansion in the field of transition metal-containing polymers. Frontiers in Transition Metal-Containing Polymers provides a comprehensive, up-to-date review of the synthesis, properties, and applications of transition metal-containing polymers, including an overview of the historical development of these types of polymers. Written by the leading researchers in the field, this thorough volume covers the routes to organometallic and coordination polymers, as well as characterization and applications of transition metal-containing monomers and polymers. Other topics discussed include: Metallo-supramolecular coordination polymers based on nitrogen ligands Coordination polymers based on phosphorus ligands Polypeptide-based metallobiopolymers and DNA-based metallopolymers Metallodendrimers Self-assembly of metal-containing block copolymers Applications including drug delivery, optics, molecular devices, sensors, conductive materials, and more
Keywords: Transition metals,Kim loại chuyển tiếp